TOWARDS AN APPROPRIATE EFFORT-BASED FISHERY MODEL FOR THE TUNA FISHERY OF MALDIVES - Kumar, R Sathiendra; Tisdell, C A (Indian Journal of Fisheries, 2011)
This paper considers the applicability of the Schaefer model and the Fox model to the tuna fishing industry of the Maldives. Examinaition of Maldiviao catch apd effort data throws doubt upon the applicability of these models to this fishing industry, which depends on a highly migratory species. An alternative production- type model based on a population threshold assumption is suggested and found to be much more consistent with Maldivian effort and catch data. Such a model may also have application to some other fisheries based on migratory species.